2018
DOI: 10.1021/acs.jced.8b00155
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior and Raman Spectroscopic Analysis for CH4 and CH4/C3H8 Hydrates Formed from NaCl Brine and Monoethylene Glycol Mixtures

Abstract: We present pure CH4 and CH4/C3H8 mixed hydrate phase equilibria formed from a mixture of NaCl (10 wt %) and monoethylene glycol (MEG, 10 and 30 wt %) solutions. As expected for thermodynamic inhibitors, the mixture of salt and glycol causes the hydrate phase equilibrium boundary to shift to lower temperatures and higher pressures, and on increasing the MEG concentration, the hydrate stable region shifted more. The measured experimental data are also compared with a thermodynamic model recently developed, named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…18 Information about the experimental and calculation procedure can be found in previously published studies. [8][9][10]13,18 In this study, a hydration number of 6 was used for pure CH 4 hydrate, which is widely accepted in the literature. 8,10,13 The hydration number for CH 4 /C 3 H 8 hydrate was calculated using eq 1:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Information about the experimental and calculation procedure can be found in previously published studies. [8][9][10]13,18 In this study, a hydration number of 6 was used for pure CH 4 hydrate, which is widely accepted in the literature. 8,10,13 The hydration number for CH 4 /C 3 H 8 hydrate was calculated using eq 1:…”
Section: Methodsmentioning
confidence: 99%
“…Pitzer’s correlation was used to determine the compressibility factor needed to analyze hydrate formation and dissociation kinetics . Information about the experimental and calculation procedure can be found in previously published studies. ,, …”
Section: Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The produced water resulting from subsurface processes contains salts such as NaCl, which also thermodynamically inhibit the hydrate formation. , As the amount of salts in produced water is not sufficient to completely prevent hydrate formation, additional MEG or MeOH is required, resulting in MEG/MeOH solutions containing NaCl. , Therefore, it is important to understand the effect of salts on hydrate formation when they coexist with MEG or MeOH. Studies on understanding the effect of MEG or MeOH in the presence of salts have mainly focused on hydrate phase equilibrium conditions. Lee and Kang studied hydrate phase equilibrium conditions of natural gas in the presence of MeOH (10–30 wt %) and MEG (10–50 wt %) with 3.5 wt % NaCl. The thermodynamic inhibition effect of MeOH was found to be better than that of MEG, and adding NaCl to MEG or MeOH solutions increased the thermodynamic inhibition effect.…”
Section: Introductionmentioning
confidence: 99%
“…Kwak et al evaluated the phase equilibrium conditions of pure CH 4 hydrate and a mixture of CH 4 and C 3 H 8 hydrate in the presence of sodium chloride (10 wt %) and monoethylene glycol (10 and 30 wt %) using the isochoric method . The experimental results showed that the hydrate phase equilibrium boundaries shifted to the lower temperatures and higher pressures with increasing the concentration of monoethylene glycol in a constant amount of sodium chloride.…”
Section: Introductionmentioning
confidence: 99%